Implementasi kebijakan rencana umum tata ruang :: Kota Administratif Banjarbaru - RIVAI, Hasmi (Universitas Gadjah Mada, 1998)
The administrative city of Banjarbaru consisting O 3 subdistrics and divided into 4 f city parts has been growing region since it is legitimated as administrative city in 1975. The prior status of the city wa subdistrict city. The near distance from the city to the capital city of South Kalamantan Province, Banjarmasin, and the superiority of natural quality of mountains which is relative level compared to the condition of the area of Banjarmasin city of swamps surounding by rivers, are the causal factors of relative rapid growing of the hinterland of the region. The administratif City of Banjarbaru becomes therefore the alternative area in developing the city of Banjarmasin into industrial centre area, governmental centre area, education centre area, and settlement centre area for the city dweller of Banjamasin and the surounding area. To give the direction in developing the city as the guideline in the short term planning, the city Main Plan has been made. The plan is then revised i n 1993 because of the rapid growing of the administrative city of Banjarbaru to be the general City Space Arrangement of the administrative City of Banjarbaru. In the General City Space Arrangement the administrative city is directed to be the city with the four concepts of regional development: industrial area, governmental area, education centre area, and the settlement area with the city development pattern and strategy to be directed to the underdeveloped area of the city than can reduce the tendency of the city physical development which takes place more in the area surounding the regional line of Banjarmasin-Banjarbaru-Martapura. The west part of the city is directed to be industrial centre, the north and the east part the city is for the governmental and education centre area and the south part of the city most of which is still unoccupied, is for the settlement area. In the implementation phase of the policy till 1997 which is the third phase of the 20 years planning periode from 1984, the concept of the area developing could actually not be well manifested that the performance of the policy is still in low level. The settlement area planned in the south part of the city was not in realization as hoped. And also the development of the education centre has not met the maximum result. The industrial centre is the only concept which has already been in realization and has significant influence on the spreading out of physical development of the city, specially the development of housing in the west part of the city. The factors concidered as the obstacles in the spreading out of physical development of the city has the pattern of multiple nuclei i n the administrative Banjarbaru. They are a combination of many factors : 1 . Resources factors. 2. The factors of the policy content. 3. The bureaucracy structure factor. 4. The social and economic environmental condition factor. 5 . The implementor attitude factor.